Between mokṣa and nirvāṇa: Archaeological traces of Siwa–Buddha harmony in Bali and their eschatological worldview - Made Ayu Diah Indira Virgiastuti; Ashutosh Pareek; Heri Purwanto; Ni Wayan Jemiwi Jero (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This article examines the eschatological worldview underlying the archaeological heritage of Siwa–Buddha traditions in Bali, focusing on how concepts of life, death, and post-mortem liberation were articulated through religious material culture. Drawing on archaeological evidence such as temple layouts, ritual iconography, and mortuary-related symbols, the study argues that Balinese Siwa–Buddha syncretism represents not merely a historical coexistence of religious traditions, but a coherent theological negotiation between two soteriological paradigms: mokṣa and nirvāṇa. Methods: This study employs a qualitative interpretative approach with an archaeological-critical and historiographical framework to examine Shiva–Buddha relations in Bali as a process of religious-cultural transformation shaping eschatological understandings of life, death, and liberation. Data were collected through archaeological observation, textual and inscriptional analysis, and theoretical literature review, and analyzed using thematic, semiotic, and historiographical deconstruction to interpret artifacts, sacred spaces, and rituals as material expressions of eschatological meaning. Findings: The findings suggest that Siwa–Buddha harmony in Bali produced an eschatological framework in which life and death were understood as a continuous process of spiritual refinement rather than as oppositional states. Architectural orientations, ritual spaces, and symbolic representations indicate a shared concern with purification, release from cyclical existence, and ultimate union with a transcendent reality. Conclusion: This synthesis challenges rigid sectarian classifications and reveals a localized eschatology that accommodated multiple paths to liberation within a single religious landscape. Novelty/Originality of this article: This study demonstrates that Southeast Asian religious heritage, particularly in Bali, offers an important case for understanding how plural religious traditions can converge in shaping shared conceptions of death, afterlife, and ultimate salvation.